TOTAL ALKALOID CONTENT , CYTOTOXICITY, AND SELECTIVITY OF ETANOL EXTRACT OF Litsea firma (Blume) Hook. F - Hidayati, Putri Risti; Muharini, Rini; Erlina, Erlina (Tanjungpura University, 2025)
Litsea firma (Blume) Hook. f., known locally as Medang Piawas, is a Lauraceae plant found in West Kalimantan, which was traditionally used as medicine and reported to contain alkaloids. This study determined the total alkaloid content in ethanol extracts of the roots, stems, and leaves. Phytochemical tests with Dragendorff, Mayer, and Wagner reagents confirmed alkaloid presence, with the highest intensity in stems, followed by leaves and roots. Quantitative analysis by UV-Vis spectrophotometry using caffeine and quinine standards showed the stem extract contained the highest alkaloid levels (18.289 mg CE/g and 2.299 mg QE/g). Cytotoxic activity was evaluated against cancer cell lines (4T1, MCF-7, T47D, WiDr, HeLa, Hep G2) and normal Vero cells using the MTT assay. The root extract exhibited weak cytotoxicity against WiDr cells (IC50 201